2009
DOI: 10.1016/s1473-3099(09)70055-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of meningitis due to antibiotic-resistant Acinetobacter species

Abstract: Acinetobacter meningitis is becoming an increasingly common clinical entity, especially in the postneurosurgical setting, with mortality from this infection exceeding 15%. Infectious Diseases Society of America guidelines for therapy of postneurosurgical meningitis recommend either ceftazidime or cefepime as empirical coverage against Gram-negative pathogens. However, assessment of the pharmacodynamics of these cephalosporins in cerebrospinal fluid suggests that recommended doses will achieve pharmacodynamic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 143 publications
3
149
0
7
Order By: Relevance
“…In a recent review, intrathecal plus systemic therapy was recommended for treatment of ANM patients. 17 Risk factors are important in predicting the outcomes of ANM patients. A case-control study showed a higher incidence of hydrocephaly in patients with Acinetobacter.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, intrathecal plus systemic therapy was recommended for treatment of ANM patients. 17 Risk factors are important in predicting the outcomes of ANM patients. A case-control study showed a higher incidence of hydrocephaly in patients with Acinetobacter.…”
Section: Discussionmentioning
confidence: 99%
“…remain very important pathogens with an increasing resistance to several antibiotic classes, a disturbing occurrence that affects patients' care all over the world. 10 The finding that almost 40% of patients who underwent craniotomy in our prospective study developed at least one infection is disturbing, and it should alert physicians and investigators to search for the factors that will help in the mitigation of such complications in neurosurgical patients.…”
Section: Microbiology Of Other Infectionsmentioning
confidence: 92%
“…is their increasing resistance to almost all antibiotic classes (including carbapenems), which has been a significant problem in the recent years. 1,4,10,16,22,25,30,36 Klebsiella spp. were the second most commonly isolated pathogens in this cohort, with the isolates carrying a high degree of resistance to third-generation cephalosporins and carbapenems (Table 4).…”
Section: Meningitismentioning
confidence: 99%
“…Although nosocomial pneumonia is the most common clinical manifestation, Acinetobacter meningitis has been increasing in frequency [3]. Acinetobacter meningitis may occur following neurosurgery, traumatic head injury or/and metastatic infection in bacteremic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of central nervous system infection due to MDRA has been reported to range from 15-71% [3]. There are very few published studies of neurological outcomes in pediatric MDRA meningitis cases [8,9].…”
Section: Introductionmentioning
confidence: 99%